Internet and network economics 7th International Workshop, WINE 2011, Singapore, December 11-14, 2011, proceedings - Chen, Ning 1979-; Elkind, Edith 1976-; Koutsoupias, Elias (Lecture notes in computer science, 2011)
This book constitutes the refereed proceedings of the 7th International Workshop on Internet and Network Economics, WINE 2011, held in Singapore, in December 2011. The 31 revised full papers and 5 revised short papers presented together with the abstracts of 3 papers about work in progress were carefully reviewed and selected from 100 submissions. The papers are orginzed in topical sections on algorithmic game theory, algorithmic mechanism design, computational advertising, computational social choice, convergence and learning in games, economics aspects of security and privacy, information and attention economics, network games and social networks.